Organic Pollutants Monitoring, Risk and Treatment - Nageeb Rashed, M. (IntechOpen, 2013)
Organic pollutants cause several environmental problems if discharged to air or water body. The occurrence of organic pollutants in the ecosystem, their risk and removal methods are very important issues .This book deals with several aspects of organic pollutants, especially in the light of organic pollutants monitoring, risk assessment as well as the practical application of different techniques for removing it from the environment. The book is divided into three sections contains 9 chapters. The first section explains monitoring of organic pollutants in soil and water. The second section discusse its risk to human, soil and plants. The third section focuse on the different treatment process for the removal of organic pollutants.